Obtaining polyhydroxyalkanoate and plastic film formation from the microalgae Chlorella vulgaris under light stress and nitrogen deficiency (Research, Society and Development, 2024)
The microalgae Chlorella vulgaris is a potential source of biomass and several biopolymers. The aim of this study was to evaluate the production of polyhydroxyalkanoate and the formation of plastic film under constant light stress (24h) and photoperiod (12/12h – light/dark), in addition to the influence of inorganic nitrogen source deficiency (NaNO3 – 50%), under cell concentration (Xm), productivity (PX) and specific growth rate (µ). The polymer was also characterized by Fourier transform infrared spectroscopy (FTIR) and thermal analysis (TGA). Autotrophic conditions (CBBM24) under constant light stress (24h) showed better results, with Xm = 1163.45 ± 52 mg L-1, PX = 145.43 ± 7 mg L-1 day-1 and µ = 0.39 ± 0.00 day-1 during 8 days of cultivation. After extraction, the polymer obtained was characterized by FTIR, showing transmittance bands located at 1722 cm-1 that were attributed to the stretching vibration of the C=O group (carbonyl ester) in the PHA polyester. Thermal analysis (TGA) showed that the polymer obtained from CBBM24 biomass showed Tonset (21%) at 91 °C and Tdecomp (76%) at 295 °C. The plastic film was also produced using glycerol plasticizer, thus demonstrating that microalgae has strong potential in the production of biodegradable plastic.